What matters most to patients about primary healthcare: mixed-methods patient priority setting exercises within the PREFeR (PRioritiEs For Research) project - Louisa Edwards; Melody Monro; Yaron Butterfield; Ravin Johl; Kent Cadogan Loftsgard; Hayley Pelletier; Colleen McGavin; M Ruth Lavergne (BMJ Open)
Objectives To identify patient-generated priority topics for future primary care research in British Columbia (BC), Canada within a diverse patient population.Design Mixed-methods priority setting exercises framed by the dialogue model, using the nominal group technique (rank-ordered scoring) and province-wide online surveys capturing importance ratings of the top 10 primary healthcare topics from patients and primary care providers.Setting BC, Canada.Participants Topic identification was completed by 10 patient partners (7 female, 3 male) from the BC Primary Health Care Research Network Patient Advisory; online surveys were completed by 464 patients and 173 primary care providers.Results The 10 members recruited to the patient advisory provided over 80 experiences of what stood out for them in BC primary care, which were grouped thematically into 18 topics, 10 of which were retained in province-wide surveys. Top-rated survey topics for both patients (n=464) and providers (n=173) included being unable to find a regular family doctor/other primary healthcare provider, support for living with chronic conditions, mental health resources and information sharing, including electronic medical records. However, all 10 topics were rated important, on average, by both groups.Conclusions The current project activities demonstrate the feasibility of including patients in priority setting exercises for primary healthcare in general, rather than focusing on a condition-specific population or disease area. There was considerable overlap between patient-generated topics and topics previously identified by other stakeholders, but patients identified two additional topics (mental health resources, improve and strengthen patient–provider communication). More similarities than differences in topic importance between patients and providers emerged in the online surveys. The project activities that follow (rapid literature reviews, multistakeholder dialogue) will highlight under-researched topics and inform the development of specific research questions.